URBAN DESIGN FOR TSUNAMI IMPACT MITIGATION; APPLICATION OF PHYSICAL ELEMENT - Tauhid, Fahmyddin A'raaf (Nature: National Academic Journal of Architecture, 2018)
Abstract_ The increasing of tsunami event has called the integration of urban design for disaster impact mitigation. The Geodynamics position of many global cities puts latter areas are highly vulnerable to earthquake followed by tsunamis. In supporting its function as the main hub in social and economic and protecting environment, the employment of urban design for tsunami impact mitigation is hypothesized as sustainable mean. Therefore, this paper seeks the possibility of employment of urban design’s physical element for tsunami impact mitigation within disaster studies field using literature and case studies for Indonesian cities context. This study recommends that Infrastructure planning and design, Coastal forest, Early warning system, Emergency road network planning, Pre-tsunami evacuation planning and Building design and construction are suitable physical element for impact mitigation. Keywords: Urban Design; Tsunami; Mitigation; Physical Element.